Avaliação da vinhaça de cana-de-açúcar para produção de hidrogênio em reator anaeróbio de leito fluidizado em condição mesofílica: efeito de co-substrato, TDH, e concentração - Reis, Cristiane Marques dos (2014)
study evaluated the production of hydrogen and methane from sugarcane vinasse in anaerobic fluidized bed reactor. Two fluidized bed reactors filled with expanded clay were operated under two different concentrations: R5 (5 gCOD.L-1) and R10 (10 g.CODL-1). During the first stage, glucose was used as the primary carbon source. Along the first step vinasse was added from 0% to 100% of the organic source under HRT of 6 h. In a second step with 100% of sugarcane vinasse, HRT was reduced to 4, 2 and 1 h. In another reactor R15 (15 gCOD.L-1) it was varied the substrate (100% glucose; 50 % glucose/ 50 % vinasse; 100 % vinasse) under HRT of 8 h. All reactors were operated in room temperature and a sludge from the treatment of swine wastewater was used. It was not observed methane production in R15. Hydrogen production rate and hydrogen yield reached, respectively: 0,01 L.h-1.L-1 e 0,10 mmolH2.g-1COD added. In reactors R5 and R10, biogas was formed by H2 and CO2 when glucose was present in the feed. Methane was formed when vinasse became the main substrate. The best operating condition occurred under HRT of 1 h, vinasse 100% at a concentration of 5 gCOD. L-1 with a hydrogen production rate of 0.57 L.h.-1L-1. As regards the yield, the best condition was under HRT of 6 h when the affluent comprised vinasse and glucose (3:1) reaching an yield of 3.07 mmolH2.g-1CODadded. Methane production in acidic conditions showed that the methanogens have adapted to a slightly acidic pH of 4.5. The principal metabolites were ethanol, butyric acid, propionic acid and methanol. Microbial characterization revealed the presence of Prevotella and Megasphaera belonging to the domain Bacteria and Methanobacterium and Methanosphaera belonging to the Archaea domain.